Optimal asset allocation of wind energy units in conjunction with demand response for a large‐scale electric grid. (19th June 2019) - Wattoo, Waqas Ahmad; Feng, Donghan; Yousif, Muhammad; Tahir, Sohaib; Anwar, Muhammad Tuoqeer; Numan, Muhammad
Summary: Demand response is considered to be a realistic and comparatively inexpensive solution aimed at increasing the penetration of renewable generations into the bulk electricity systems. The work in this paper highlights the demand response in conjunction with the optimal capacity of installed wind energy resources allocation. Authors proposed a total annual system cost model to minimize the cost of allocating wind power generating assets. This model contains capacity expansion, production, uncertainty, wind variability, emissions, and elasticity in demand to find out cost per hour to deliver electricity. A large‐scale electric grid (25 GW) is used to apply this model. Authors discovered that demand response based on interhourly system is not as much helpful as demand response grounded on intrahourly system. According to results, 32% wind generation share will provide the least cost. It is also worth noting that optimal amount of wind generation is much sensitive to installation cost as well as carbon tax. Abstract : Optimal wind planning model in conjunction with demand response is presented. Adding wind energy resources can reduce uncertainty costs more than production costs. Interhourly demand response is not as useful as intrahourly demand response. Optimal wind resource level is as sensitive to carbon tax as to first cost.